Head-to-Head Comparison of 68Ga-PSMA-11 and 131I in the Follow-Up of Well-Differentiated Metastatic Thyroid Cancer: A New Potential Theragnostic Agent - Pitalua-Cortes, Quetzali; García-Perez, Francisco Osvaldo; Vargas-Ahumada, Joel; Gonzalez-Rueda, Sofia; Gomez-Argumosa, Edgar; Ignacio-Alvarez, Eleazar; Soldevilla-Gallardo, Irma; Torres-Agredo, Liliana (Frontiers in Endocrinology, 2021)
Introduction Thyroid cancer is the main endocrine neoplasia worldwide, for which 131I therapy is the cornerstone treatment. One of the main problems of follow up in patients with this type of cancer, is the need for thyroglobulin stimulation, not to mention the poor availability of 123I or 124I, to perform studies with a higher degree of sensitivity. Prostatic Specific Membrane Antigen (PSMA) PET/CT has demonstrated to be quite useful in a diversified number of neoplasms, on behalf of its capacity of evaluating the extent of type II carboxypeptidase expression in vascular endothelium. The end point of this article is to assess whether this novel image method possesses applicability in thyroid neoplasms follow up, for diagnostic and potentially therapeutic purposes. Methods We retrospectively evaluated well differentiated metastatic thyroid cancer patients, who underwent a post therapeutic 131I dose whole body scan (WBS) and complementary SPECT/CT, as well as 68Ga-PSMA–11 PET/CT. Results Ten patients with differentiated thyroid cancer were included, of whom 80% were women and 20% men, mean age was 58 years old (± 11.6). Sixty-four metastatic lesions were analyzed, 67.19% had papillary histology and 32.81% were follicular type, the most affected site of metastases was bone in 57.81%, followed by lung 17.19%, lymph nodes 7.81%, postoperative thyroid bed 4.69%, brain 4.69% and others 7.81%. 68Ga PSMA-11 PET/CT detected 64/64 lesions, all of them also identified by computed tomography (CT), whereas 131I SPECT/CT detected 55/64 lesions. Discrepant lesions were localized in lung 44.4%, brain 22.2%, postoperative thyroid bed 11.1%, lymph nodes 11.1% and bone 11.1%. The degree of correspondence among observers was outstanding for both radiotracers, but close upon perfect for PSMA-11 (κ = 0.98; 95% CI, 0.80 – 0.91), as opposed to 131 I (κ = 0.86; 95% CI, 0.71 – 0.76). Conclusions 68Ga-PSMA PET/CT showed an utterly superior capability for metastatic lesion detection when compared to 131I SPECT/CT. These findings suggest that PSMA PET/CT could possibly and precociously identify radioiodine refractoriness. PSMA uptake values not only expedite diagnosis, but also award it the ability to be used for therapeutic intents.